KRCC1: A potential therapeutic target in ovarian cancer. Issue 2 (23rd December 2019) - Dwivedi, Shailendra Kumar Dhar; Shameer, Khader; Dey, Anindya; Mustafi, Soumyajit Banerjee; Xiong, Xunhao; Bhattacharya, Udayan; Neizer‐Ashun, Fiifi; Rao, Geeta; Wang, Yue; Ivan, Cristina; Yang, Da; Dudley, Joel T.; et al.
Abstract: Using a systems biology approach to prioritize potential points of intervention in ovarian cancer, we identified the lysine rich coiled‐coil 1 (KRCC1), as a potential target. High‐grade serous ovarian cancer patient tumors and cells express significantly higher levels of KRCC1 which correlates with poor overall survival and chemoresistance. We demonstrate that KRCC1 is predominantly present in the chromatin‐bound nuclear fraction, interacts with HDAC1, HDAC2, and with the serine‐threonine phosphatase PP1CC. Silencing KRCC1 inhibits cellular plasticity, invasive properties, and potentiates apoptosis resulting in reduced tumor growth. These phenotypes are associated with increased acetylation of histones and with increased phosphorylation of H2AX and CHK1, suggesting the modulation of transcription and DNA damage that may be mediated by the action of HDAC and PP1CC, respectively. Hence, we address an urgent need to develop new targets in cancer.